Agama dan Perubahan Sosial Perspektif Mukti Ali (W. 2004 M) - Nur Laila Nasution; Dahlia Lubis; Muhammad Faishal (Dinasti Review, 2024)
One of the figures in Indonesian religious studies who deserves to be studied is Mukti Ali. His ideas about religion in the context of social change have an impact on social and religious life in Indonesia. Mukti Ali has implemented his ideas in his vision as Minister of Religious Affairs of the Republic of Indonesia in the development cabinet I (1971-1973), and II (1973- 1978). This research aims to further explore how religion and social change in Mukti Ali's perspective. This research is a literature study with descriptive qualitative method. The study found that Mukti Ali considers religion as a source of values and norms that influence people's social behavior. Religion is not only a spiritual guide for individuals, but also provides a moral foundation that underlies their actions in daily life. These values and norms then shape the social order in society. Mukti Ali also states that religion not only maintains the social status quo, but can also be an agent of social change. Religion is often a source of inspiration for social movements, reform, or resistance to social injustice. Mukti Ali highlighted the complex dynamics between religion and social structures. Religion does not stand alone, but engages in complex interactions with social factors such as politics, economics and culture. Changes in social structure can affect religious interpretation and practice, and conversely, religion can also affect social change through its influence on people's beliefs and values. Thus, Mukti Ali's views on religion and social change reflect a deep understanding of the complexity of the relationship between religion and society.